1992
DOI: 10.1037/h0095690
|View full text |Cite
|
Sign up to set email alerts
|

New Day, Inc., of Spartanburg: Hospitalization study.

Abstract: All persons included in the study have a psychiatric disability due to severe and persistent mental illness, are adults in the age range of 22 to 50 years, and are members of New Day Clubhouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In one of the few studies of staff members, Finch & Kranz (1991) found that staff at Fountain House had longer tenure and fewer symptoms of bum-out than staff in traditional mental health settings. Most previous work is descriptive, and only two studies have undertaken methodologically sophisticated investigations (Wilkinson, 1992;Rosenfield & Neese-Todd, 1993). Wilkinson (1992) studied 32 clubhouse members, from the New Day Clubhouse in Spartanburg, South Carolina, comparing their frequency of hospitalization during the period before regular membership with the period of regular membership.…”
Section: Previous Empirical Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one of the few studies of staff members, Finch & Kranz (1991) found that staff at Fountain House had longer tenure and fewer symptoms of bum-out than staff in traditional mental health settings. Most previous work is descriptive, and only two studies have undertaken methodologically sophisticated investigations (Wilkinson, 1992;Rosenfield & Neese-Todd, 1993). Wilkinson (1992) studied 32 clubhouse members, from the New Day Clubhouse in Spartanburg, South Carolina, comparing their frequency of hospitalization during the period before regular membership with the period of regular membership.…”
Section: Previous Empirical Investigationsmentioning
confidence: 99%
“…Most previous work is descriptive, and only two studies have undertaken methodologically sophisticated investigations (Wilkinson, 1992;Rosenfield & Neese-Todd, 1993). Wilkinson (1992) studied 32 clubhouse members, from the New Day Clubhouse in Spartanburg, South Carolina, comparing their frequency of hospitalization during the period before regular membership with the period of regular membership. Hospital days, the number of admissions, and average length of stay were all markedly reduced in the clubhouse period.…”
Section: Previous Empirical Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 10 of the 16 studies provide enough information confirming that the organization concerned fits the certified Clubhouse Model. The other studies (Beckel, 1998;Boyd, 1997;Pernice-Duca & Onaga, 2009;Warner, Huxley, & Berg, 1999;Wilkinson, 1992) do not provide enough information confirming that the organization concerned corresponds to the "ICCD model certification." Nevertheless, we chose to include these studies, supposing that (and taking into account indirect evidence in these articles) the studied clubhouses correspond to the traditional Clubhouse Model.…”
Section: Methodsmentioning
confidence: 90%
“…However, only 10 of the 16 studies provide enough information confirming that the organization concerned fits the certified Clubhouse Model. The other studies (Beckel, 1998; Boyd, 1997; Pernice-Duca & Onaga, 2009; Warner, Huxley, & Berg, 1999; Wilkinson, 1992) do not provide enough information confirming that the organization concerned corresponds to the “ICCD model certification.” Nevertheless, we chose to include these studies, supposing that (and taking into account indirect evidence in these articles) the studied clubhouses correspond to the traditional Clubhouse Model. However, one study provides information that indicates that it does not fit with the Clubhouse Model (Yildiz, Tural, Kurdoğlu, & Emin Onder, 2003): This clubhouse is not certified and is managed by members and their families, contrary to standard practices in the Clubhouse Model.…”
Section: Methodsmentioning
confidence: 91%